Compact Microstrip Bandpass Diplexer Based on Twist Revised Split Ring Resonators - Jian Li; Yongjun Huang; Xuefeng Zhao; Guangjun Wen (International Journal of Antennas and Propagation)
Based on the twist revised split ring resonators (TR-SRRs) inspired filter unit a microstrip bandpass diplexer with highly compact size and high frequency selection and isolation properties is synthesized and systematically characterized. The proposed filter unit exhibits both electric and magnetic coupling effects and possesses two resonance modes (magnetic and electronic resonances). The two resonance modes can be flexibly controlled by adjusting the gap between the two TR-SRRs. The synthesized diplexer has very simple configuration with size of 0.217λd×0.217λd and degree of freedom for impedance matching. Measurement and simulation demonstrations are performed in this paper and a good agreement is achieved. The measured results indicate two quite close frequency channels (centered at 2.16 GHz and 2.91 GHz) with isolation larger than 30 dB. The proposed diplexer can be easily integrated into miniaturized RF/microwave integrated circuits.